The Influence of E-Government Implementation in Public Services on Performance Effectiveness and Professor Satisfaction at the University of Jember - Jarkasi Jarkasi; Djoko Poernomo; Abubakar Eby Hara (Universitas KH. Abdul Chalim Mojokerto, 2025)
The implementation of E-Government based services is expected to provide added value to public services. Jember University as a higher education institution implements E-Government through the Integrated Information System (SISTER) application or sister.unej.ac.id. The purpose of the study is to know and explain the effect of the Implementation of E-Government Public Service on the effectiveness of professor performance and professor satisfaction. This study uses a quantitative approach. The population of this study is all professors of the University of Jember who are active until 2023 as many as 88 people and the samples is 72 people was carried out using a simple random sampling method. Data analysis uses path analysis with a linear regression approach. The results of the study prove that there is an effect of Implementation of E-Government Public Service on the effectiveness of the performance and the satisfaction of professors. There is an effect of the effectiveness of professor performance on the satisfaction of professors. The research findings provide practical implications, that the University of Jember always pays attention to matters especially those related to the Implementation of Public Service E-Government. This means that theoretically, this research opens up opportunities for future research agendas to develop concepts with other variables such as facilities and infrastructure, trust, accountability, and others.